Predictors of work-related eye injuries among stone quarry workers in the Ashanti Region of Ghana: A cross-sectional study - Gyekye Adu Boahen; Adolphina Addo-Lartey; Mohammed Abdul Gafaru; Edwin Afari; Maxwell Hubert Antwi; George Nkrumah Osei (Journal of Interventional Epidemiology and Public Health)
Introduction: The occurrence of eye issues among quarry workers in southern Ghana is significant, with 58% reporting irritation and 9.4% experiencing quarry-related eye problems. This study assessed factors associated with work-related eye injuries among stone quarry workers in the Ashanti Region of Ghana.